2014
DOI: 10.4103/0973-8398.143932
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of anti-ulcer activity of monoammonium glycerrhizin and Aloe vera gel powder through a novel drug delivery system

Abstract: U sual treatment for Helicobacter pylori-induced peptic ulcer includes a 14-day "triple therapy" of two antibiotics and a proton pump inhibitor. However, the current therapy has side-effects like stomach upset, non-compliance, incomplete absorption of drug and antibiotic resistance. To overcome these limitations, there is a need to suggest an alternative therapy. The best possible alternative is to deliver herbal constituents. The purpose of the present study was to optimize the efficacy of herbal constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Pharmacodynamic studies in rats showed that the combination of MG and Aloe vera gel gave 99% ulcer inhibition in comparison with 51% ulcer inhibition in the group administered with MG alone. X-ray studies in rabbits proved the gastroretension of the tablet for more than 6 h. This suggests relevance of novel drug delivery system in delivery of herbal constituents in the treatment of gastric ulcer [22] . Pereira GG.…”
Section: The Bioavailability Of Coq10 With Aloe Veramentioning
confidence: 91%
“…Pharmacodynamic studies in rats showed that the combination of MG and Aloe vera gel gave 99% ulcer inhibition in comparison with 51% ulcer inhibition in the group administered with MG alone. X-ray studies in rabbits proved the gastroretension of the tablet for more than 6 h. This suggests relevance of novel drug delivery system in delivery of herbal constituents in the treatment of gastric ulcer [22] . Pereira GG.…”
Section: The Bioavailability Of Coq10 With Aloe Veramentioning
confidence: 91%
“…Pharmacodynamic studies in rats showed that the combination of MG and Aloe vera gave 99% ulcer inhibition in comparison with 51% ulcer inhibition in the group administered with MG alone. X-ray studies in rabbits proved the gastroretention of the tablet for more than 6 h. This suggests relevance of novel drug delivery systems in delivery of herbal constituents in the treatment of gastric ulcer [14] .…”
Section: Known Aloe's Immune Efficacymentioning
confidence: 93%
“…but the tablet disintegrated immediately in the dissolution media. HPMC E5 which is a low viscosity grade polymer, gels with low swelling ability and thus didn't trapped carbon dioxide therefore the tablet ruptured after floating immediately (41) . Sodium alginate that used in FMT2 failed in achieving floating tablet.…”
Section: ) Physical Parameters Of Bfn Floating Microsponge Tabletsmentioning
confidence: 99%